THỬ NGHIỆM TỰ NHIÊN ĐÁNH GIÁ ĐỘ BỀN KHÍ HẬU CỦA MỘT SỐ SẢN PHẨM SƠN TƯỜNG TRONG MÔI TRƯỜNG KHÍ HẬU NHIỆT ĐỚI VIỆT NAM - Nguyễn, Chí Cường; Phan, Hữu Luyện; Lê, Đức Mạnh; Phan, Ngọc Tú; Đặng, Văn Đông (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
OUTDOOR WEATHERING FOR DETERMINATION OF DECORATIVE AND PROTECTIVE PROPERTIES OF SOME EMULSION PAINTS BEING USED IN VIETNAM’S TROPICAL CLIMATE This article presents result of outdoor weathering for determination of decorative and protective properties of eight exterior paints: EPR, SPH, JTJ, TOS, NPW, DLW, TSS, DSF and three interior paints: IDLA, INPO, IKVA. The experiment was implemented at three outdoor exposure sites for four years continuously. The results showed that all samples did not appear blistering, flaking, checking, cracking, peeling, dirt collection or fungal growth. Samples of three interior paints were not exhibited any significant coating degradation. Samples of eight exterior paints have low initial gloss values, therefore they had no significant change in gloss. However, the phenomenon of chalking, color change takes place strongly throughout the experiment. Affirming that the decorative characteristics of the exterior emulsion paints have been significantly reduced after 4 years of outdoor weathering in the tropical climate of Vietnam.